Penebaran Benih Ikan Di Bendung Kedungdowo Kramat Kabupaten Batang - Nur Fadhilah Adimahsyaf; Dzulfiqar Ammar Syam; Tri Yusufi Mardiana; Linayati (CV. SINAR HOWUHOWU, 2024)
Kedungdowo Kramat Weir is one of the weirs in Batang which functions to regulate and channel air supplies for agriculture, fisheries and other fields. This wie is also widely used as an affordable tourist destination. Currently there are complaints regarding incidents of fishing using illegal fishing gear such as electrocution. Therefore, there are indications of a decline in the biota population. The existence of fish is very important as a source of animal protein to fulfill the nutrition of the community, especially children. Management efforts are needed to create an increase in fish populations in the Kedungdowo Kramat Weir. An example of an effort that can be made is by stocking fish. The stages of this seed stocking activity include submitting an application for stocking fish seeds, location survey, collecting fish seeds, and stocking fish seeds. This activity was carried out on Friday, August 30 2024 by the District Marine Fisheries and Livestock Service. Batang collaborates with BBI Sojomerto, South Proyonanggan Village, Pokmaswas Kramat Kedung Segowok, and the South Proyonanggan Village Community. The fish stocked are 2,000 tilapias measuring 4-6 cm. Restocking activity was well received and received a positive response from all parties in the local community. The results of this activity are expected to increase the fish population and improve the environmental sustainability of the aquatic ecosystem at Kedungdowo Kramat Weir.